Bortezomib has little ex vivo activity in chronic myeloid leukemia: individual tumor response testing comparative study in acute and chronic myeloid leukemia - Styczyński, Jan; Gil, Lidia; Czyżewski, Krzysztof; Kołodziej, Beata; Kuryło-Rafińska, Beata; Lewandowski, Krzysztof; Gniot, Michał; Lewandowska, Maria; Komarnicki, Mieczysław; Wysocki, Mariusz (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: Resistance to imatinib is one of the most important issues in treatment of chronic myeloid leukemia (CML) patients. The objective of the study was to analyze the ex vivo drug resistance profile to bortezomib and 22 other antileukemic drugs, including three tyrosine kinase inhibitors (TKIs), in CML in comparison to acute myeloid leukemia (AML). Material and methods : A total of 82 patients entered the study, including 36 CML and 46 AML adults. Among CML patients, 19 had advanced disease, 16 were resistant to imatinib, and 6 had ABL-kinase domain mutations. The ex vivo drug resistance profile was studied by the MTT assay. Results: CML cells were more resistant than AML blasts to the following drugs: prednisolone, vincristine, doxorubicin, etoposide, melphalan, cytarabine, fludarabine, thiotepa, 4-HOO-cyclophosphamide, thioguanine, bortezomib, topotecan, and clofarabine. CML cells were 2-fold more sensitive to busulfan than AML cells. CML patients with clinical imatinib resistance had higher ex vivo resistance to vincristine, daunorubicin, etoposide, and busulfan. No significant differences to all tested drugs, including TKIs, were observed between CML patients with non-advanced and advanced disease. CML patients with mutation had higher ex vivo resistance to vincristine, idarubicin, thiotepa, and busulfan. Conclusions : CML cells are ex vivo more resistant to most drugs than acute myeloid leukemia blasts. Busulfan is more active in CML than AML cells. In comparison to AML cells, bortezomib has little ex vivo activity in CML cells. No differences between CML subgroups in sensitivity to 3 tested TKIs were detected.